A Case Report of Mania and Psychosis Five Months after Traumatic Brain Injury Successfully Treated Using Olanzapine. (12th June 2017) - Cittolin-Santos, Giordano F.; Fredeen, Jesse C.; Cotes, Robert O.
Abstract : Background . There are few published pharmacologic trials for the treatment of acute mania following traumatic brain injury (TBI). To our knowledge, we present the first case report of an individual being treated and stabilized with olanzapine monotherapy for this condition. Case Presentation . We describe the case of a 53-year-old African American male admitted to an inpatient psychiatric hospital with one month of behavioral changes including irritability, decreased need for sleep, hyperverbal speech, hypergraphia, and paranoia five months after TBI. Using Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) criteria, he was diagnosed with bipolar disorder due to traumatic brain injury, with manic features. He was serially evaluated with clinical rating scales to measure symptom severity. The Young Mania Rating Scale (YMRS) score upon admission was 31, and the Clinician-Rated Dimensions of Psychosis Symptom Severity (CRDPSS) score was initially 9. After eight days of milieu treatment and gradual titration of olanzapine to 15 mg nightly, his symptoms completely abated, with YMRS and CRDPSS scores at zero on the day of discharge. Conclusion . Olanzapine was effective and well tolerated for the treatment of mania following TBI.